2014
DOI: 10.1007/s13197-014-1280-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characteristics of goldenberry fruit (Physalis peruviana L.)

Abstract: Some physical and chemical characteristics of goldenberry fruit (Physalis peruviana L.) were investigated. These characteristics are necessary for the design of equipments for harvesting, processing, transportation, sorting, separating and packing. The fruit length, diameter, geometric and arithmetic mean diameters, sphericity, surface area, projected areas (vertical-horizontal) and aspect ratio of goldenberries were determined as 17.52 mm, 17.31 mm, 17.33 mm, 17.38 mm, 98.9 %, 0.949 cm 2 , 388.67-387.85 mm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
4
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 25 publications
7
36
4
11
Order By: Relevance
“…Table 1 also presented the values for the firmness, this parameter reflects the integrity of the pericarp tissue, wherein the value obtained is 7.84 and 6.55 N for fruit grown in Lam Ha and Don Duong, respectively. Yıldız et al (2015) presented that the average skin hardness of the goldenberry fruit in their study was 8.01 N, it is quite similar to our obtained results. However, Trinchero et al (1999) found that the firmness of the physalis berries in their study was 3.42±0.32 N, this value obtained somewhat lower than that referenced by the authors, even when compared to our results.…”
Section: Physical Properties Of Goldenberrysupporting
confidence: 91%
See 2 more Smart Citations
“…Table 1 also presented the values for the firmness, this parameter reflects the integrity of the pericarp tissue, wherein the value obtained is 7.84 and 6.55 N for fruit grown in Lam Ha and Don Duong, respectively. Yıldız et al (2015) presented that the average skin hardness of the goldenberry fruit in their study was 8.01 N, it is quite similar to our obtained results. However, Trinchero et al (1999) found that the firmness of the physalis berries in their study was 3.42±0.32 N, this value obtained somewhat lower than that referenced by the authors, even when compared to our results.…”
Section: Physical Properties Of Goldenberrysupporting
confidence: 91%
“…The sphericity of goldenberry in this study varied from 107.13 to 111.66% and 108.32 to 113.20% for fruits grown in Lam Ha and Don Duong, with the mean values of 111.55 and 108.71%, respectively. These values of goldenberries were higher than that of goldenberry sphericity reported by Yıldız et al (2015), just around 91.5 to 107.6 %.…”
Section: Physical Properties Of Goldenberrycontrasting
confidence: 65%
See 1 more Smart Citation
“…The most important physical properties of agricultural products include characteristic of dimensions, mass, volume, surface area, image surface, coefficient of sphericity, aspect ratio, porosity, and static friction coefficient. The most important mechanical properties include yield force, deformation, hardness, and breakdown energy (Işıklı, Şenol, & Çoksöyler, ; Jahanbakhshi, ; Jahanbakhshi, Abbaspour‐Gilandeh, & Gundoshmian, ; Jahanbakhshi & Kheiralipour, ; Yıldız, İzli, Ünal, & Uylaşer, ). Wastage rate in agricultural products will increase directly or indirectly by mechanical damage.…”
Section: Introductionmentioning
confidence: 99%
“…Physalis, or cape gooseberry or golden berry (Physalis peruviana L.) is an exotic fruit which originated in South America, but is currently commercialised in several tropical and subtropical countries (İZLI et al, 2014;SALAZAR et al, 2008;YILDIZ et al, 2015). The berries are annual or short-lived perennial and the plant can grow to up to 1.8 m. The fruit is protected by an accrescent calyx and covered by a brilliant yellow peel (PUENTE et al, 2011).…”
Section: Introductionmentioning
confidence: 99%